Legal Review of Adopted Children's Inheritance Rights from the Perspective of Civil Law in Indonesia - Yuhelson Yuhelson (Faculty of Law, Universitas Pekalongan, 2023)
Adopted children are often a complex subject in the inheritance law system, because of their position between two families, namely the biological family and the adoptive family. This research will examine the legal framework governing the inheritance rights of adopted children, evaluate conflicts that may arise between civil law and social practice, and offer legal solutions or recommendations that can balance the interests involved. This research uses a qualitative approach with descriptive methods. The research results show that adoption has a major impact on the position of adopted children's inheritance rights in civil law. Although the adoption process through the courts can provide stronger legal certainty regarding the inheritance rights of adopted children, there are variations in local legal provisions that influence the recognition and allocation of inheritance rights of adopted children. The importance of a clear and official legal process in regulating the status of adopted children is emphasized to ensure legal certainty and protection of their inheritance rights. Apart from that, gifts and wills also play an important role in the distribution of inheritance, but the calculation of legitimacy must be taken into account to ensure fairness in inheritance allocation. Thus, protection of the inheritance rights of adopted children needs to be strengthened by considering various legal aspects related to the inheritance process, to maintain justice, sustainability and peace in inherited families.